Phase change materials for thermal energy storage in industrial applications - Franklin R. Martínez; Emiliano Borri; Saranprabhu Mani Kala; Svetlana Ushak; Luisa F. Cabeza (Heliyon, 2025)
This study reports the results of the screening process done to identify viable phase change materials (PCMs) to be integrated in applications in two different temperature ranges: 60–80 °C for mid-temperature applications and 150–250 °C for high-temperature applications. The comprehensive review involved an extensive analysis of scientific literature and commercial material datasheets. A total of 65 PCMs for mid-temperature applications and 36 PCMs for high-temperature applications were identified through this extensive search. Moreover, an extensive experimental characterization of 14 preselected PCMs is included. Experimental techniques including differential scanning calorimetry (DSC), thermogravimetric analysis (TGA) and hot disk were used. The values obtained were compared to the ones found in the available literature and technical datasheets to see potential differences in the thermal behavior.